A Rare Case of Paratesticular Leiomyosarcoma - Shankar Haran; Vikram Balakrishan; Greg Neerhut (Case Reports in Urology)
Paratesticular leiomyosarcomas are rare and can lead to significant morbidity and mortality, if inadequately diagnosed or treated. We present a case of paratesticular leiomyosarcoma in an 88-year-old man presenting with a left scrotal mass with ultrasound revealing that the mass is extratesticular. Left radical orchidectomy was performed and pathological examination of the resected specimen confirmed the diagnoses of high grade leiomyosarcoma with surgical margins clear of tumour. The patient was free of metastatic disease on further imaging and has been disease-free for 18 months. A review of the literature regarding paratesticular leiomyosarcoma presentation, diagnosis, and treatment is also discussed.